Genetic Variants of HOTAIR Associated With Colorectal Cancer Susceptibility and Mortality - Kim, Jung Oh; Jun, Hak Hoon; Kim, Eo Jin; Lee, Jeong Yong; Park, Han Sung; Ryu, Chang Soo; Kim, Seungki; Oh, Doyeun; Kim, Jong Woo; Kim, Nam Keun (Frontiers in Oncology, 2020)
In colorectal carcinogenesis, the unique molecular and genetic changes that occur within cells result in specific CRC phenotypes. The involvement of the long non-coding RNA, HOTAIR, in cancer development, progression, and metastasis is well-established. Various studies have reported on the contribution of HOTAIR to cancer pathogenesis. Therefore, we selected four HOTAIR polymorphisms (rs7958904G>C, rs1899663G>T, rs4759314A>G, and rs920778T>C) to evaluate the association of each variant with CRC prevalence and prognosis. We conducted a case–control study of 850 individuals to identify the genotype frequencies of each polymorphism. The study population included 450 CRC patients and 400 control individuals that were randomly selected following a health screening. Notably, rs7958904 and rs1899663, their hetero genotype, and the dominant model were significantly different when compared to the healthy control group (rs7958904; AOR = 1.392, 95% CI = 1.052–1.843, P = 0.021). To evaluate the effect of HOTAIR polymorphisms on the survival rate, we analyzed patient mortality and relapse occurrence within 3 and 5 years with Cox-regression analysis. The rs7958904 CC polymorphism mortality rate was significantly higher than the GG polymorphism mortality rate (adjusted HR = 2.995, 95% CI = 1.189–7.542, P = 0.021). In addition, the rs920778 CC genotype was significantly different than the TT genotype (adjusted HR = 3.639, 95% CI = 1.435–9.230, P = 0.007). In addition, this study confirmed that genetic variants of HOTAIR alter the mRNA expression level (P < 0.01). We suggest that HOTAIR rs7958904G>C which is associated with CRC prevalence and mortality is a potential biomarker for CRC. The association between HOTAIR gene polymorphisms and CRC prevalence were reported for the first time.